Pengaruh Debt to Equity Ratio,.Earning Per Share,.dan.Net Profit Margin Terhadap Harga Saham pada Industri Manufaktur Konsumsi Makanan dan Minuman - Rafida Khairani; Muhammad Fikri Haikal; Siti Ramadhani; Nana Gustia; Febry Rizky Al Fadilla Sitompul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Manufacturing companies are considered to have promising developments because they can provide innovations that are well accepted by the market share. This research aims to find out the effect of DER, .EPS,. And NPM on share prices according to partial and simultaneous. The object of research is the food and beverage manufacturing industry listed on the Indonesia Stock Exchange in 2014-2018. The method of analysis used is the classical assumption test, such as 1. Normality test, heteroscedasticity test, autocorrelation test, multicollinearity test. 2. Multiple linear regression test and 3. Hypothesis testing using t-test, F-test, and the coefficient of determination (R2). The results of the research are partial DER..and..EPS does not have an impact on stock prices, while NPM has an impact on stock prices. According to DER, EPS and NPM simultaneously have an impact on stock prices. The coefficient of determination shows that 53.4% ​​of the stock price is influenced by the three independent variables. Keywords: Debt to Equity Ratio, Earning Per Share, Net Profit Margin, and Share Price